2009
DOI: 10.1086/597545
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antibacterial Use in Hospitalized Pediatric Patients in United States Academic Health Centers

Abstract: Trends in pediatric antibacterial use were examined in 20 academic health centers during the period 2002-2007. There was a significant increase in the use of linezolid (P < .001) and of macrolides (P = .001) and a significant decrease in the use of aminoglycosides (P < .001) and of first-generation cephalosporins (P < .001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 9 publications
3
31
1
1
Order By: Relevance
“…21 Similar to our study, the most commonly used antibacterial classes were beta-lactamase labile penicillins, aminoglycosides, third-generation cephalosporins, and glycopeptides. Although the patient population was not similar between the 2 studies, they showed that DOT per 1000 patientdays is a useful tool and allows solid benchmarking.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…21 Similar to our study, the most commonly used antibacterial classes were beta-lactamase labile penicillins, aminoglycosides, third-generation cephalosporins, and glycopeptides. Although the patient population was not similar between the 2 studies, they showed that DOT per 1000 patientdays is a useful tool and allows solid benchmarking.…”
Section: Discussionsupporting
confidence: 78%
“…One DOT represents the administration of a single agent on a given day, regardless of the number of doses administered or dosage strength. 21,24,25 These data were normalized to 1000 patient-days. In addition, we defined TD as days with an antibiotic treatment, irrespective of the number of antibiotics administered on the same day.…”
Section: Antibiotic Usementioning
confidence: 99%
See 1 more Smart Citation
“…19 A similar result was found recently in a study of hospitalized pediatric patients in which linezolid and macrolide use significantly increased over time; there were no reductions in other antibiotic use from 2002 to 2007. 18 In our experience, implementation of a comprehensive ASP led to significant reductions of both targeted and nontargeted antimicrobials and modifications of the patterns of antimicrobial use after ASP implementation. Total antimicrobial use decreased by 38% despite a 7% increase in the acuity of patient care from 2004 to 2007.…”
Section: Discussionmentioning
confidence: 88%
“…[11][12][13][14][15][16][17] Furthermore, beyond reporting proportions of hospitalized children who have received antimicrobials during their hospitalization, complete data about the extent of antimicrobial use in pediatric hospitals before and after ASP implementation do not currently exist. 18 Since introducing an ASP in 2004, we have prospectively evaluated its effect on antimicrobial use, physician interventions, patient outcomes, and rates of antimicrobial resistance. To the best of our knowledge, this is the first publication to thoroughly describe the impact of an ASP in a children's hospital.…”
mentioning
confidence: 99%